2013
DOI: 10.1016/j.jtcvs.2011.10.094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of institutional volumes on operative outcomes for aortic root replacement in North America

Abstract: Patients undergoing elective aortic root or combined aortic valve-ascending aortic surgery at North American hospitals that performed fewer than 30 to 40 of such procedures annually have greater risk-adjusted mortality than those undergoing surgery in higher volume hospitals. Causative factors for this inverse association between hospital volume and mortality deserve additional analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 16 publications
4
98
0
3
Order By: Relevance
“…This inherent selection bias will be impossible to eliminate from any future study. Furthermore, because valve sparing surgery is a technically demanding procedure, centers with low volumes are likely to have worse outcomes (35). Therefore the procedure should be carried out in centers with sufficient expertise.…”
Section: Discussionmentioning
confidence: 99%
“…This inherent selection bias will be impossible to eliminate from any future study. Furthermore, because valve sparing surgery is a technically demanding procedure, centers with low volumes are likely to have worse outcomes (35). Therefore the procedure should be carried out in centers with sufficient expertise.…”
Section: Discussionmentioning
confidence: 99%
“…In USA, the highest number of root operations are done in only few centers, by these regular guests (5). The rest of the centers are exposed to less than six roots per year!…”
Section: Viewpoint On Cardiac Surgerymentioning
confidence: 99%
“…47 Similarly, high volume hospitals have lower mortality rates than low volume hospitals 40 with a suggested hinge point of 100 operations/year. 47 For aortic or combined aortic valve and root procedures, one study 50 found that mortality increased exponentially in hospitals performing fewer than 40 procedures per annum. For TAVI, better results (including early mortality and rates of readmission) have been shown for hospitals that undertake >20 procedures/ year.…”
Section: Volumesmentioning
confidence: 99%